Electrode paste and preparation method thereof

By adding non-ionic surfactant and stabilizer to the electrode paste of mineral heat furnace, the problem of segregation and hollowing of the electrode paste is solved during the roasting process, the uniformity and stability of the electrode structure are improved, and the electrode flow paste and fracture are avoided.

CN119774916APending Publication Date: 2025-04-08AIKEN CARBON (CHINA) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411957154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When adding electrode paste to the existing ore furnace electrode, the operation is improper, which easily leads to segregation or cavity when liquid forms during the roasting process, resulting in different electrode paste density, resulting in electrode flow paste and electrode soft breakage.

Method used

Add nonionic surfactant and stabilizer to the electrode paste to reduce the surface energy of each component during the low-temperature calcination of the electrode paste, improve its fluidity and uniformity, prevent excessive or too small fluidity, and ensure uniformity and stability of the electrode structure.

Benefits of technology

By improving the fluidity and uniformity of the electrode paste, avoiding the problems of hollowing and density unevenness caused by uneven fluidity during the calcination process, ensuring the density and stability of the electrode structure, and avoiding electrode breakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216159010000051
    Figure BDA0005216159010000051
  • Figure BDA0005216159010000061
    Figure BDA0005216159010000061
Patent Text Reader

Abstract

The present invention provides an electrode paste and a preparation method thereof. The raw materials for preparing the electrode paste include, by weight, 70.9% to 72% of a main material, 26% to 27% of a binder, 0.9% to 3.0% of a nonionic surfactant, and 0.21% to 0.53% of a stabilizer. The present invention reduces the surface energy of each component in the liquid state formed during the low-temperature roasting process of the electrode paste by adding a nonionic surfactant to the electrode paste, thereby improving its fluidity, helping the electrode paste to be evenly distributed during the roasting process, ensuring the uniformity of the electrode structure, and avoiding the occurrence of voids in the electrode paste due to uneven fluidity during the roasting process. In order to prevent excessive fluidity, a stabilizer is also added, which can interact with the components in the electrode paste to adjust its fluidity. The electrode paste maintains appropriate fluidity during the roasting process to prevent the electrode paste from segregating due to excessive fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode paste used in an electric arc furnace, and in particular to an electrode paste and a preparation method thereof. Background Art

[0002] Different from the electrode paste used in battery materials, the electrode paste in the submerged arc furnace is a semi-finished electrode material made of aggregates such as calcined anthracite and calcined petroleum coke, as well as binders such as coal tar and tar. It is mainly used in submerged arc furnaces for the production of pig iron, ferroalloys, metallic silicon, calcium carbide and other products as a raw material for continuous self-baking electrodes. In the submerged arc furnace, the role of the electrode paste is to form electrodes by being loaded into electrode barrels and after melting, roasting and densification, and then effectively introducing electrical energy from the transformer into the smelting area in the furnace to complete the smelting process. The electrode paste is the basic material for the continuous electrode.

[0003] The core of the operation of the submerged arc furnace is to ensure that the electrode paste can be smoothly transformed into a stable working electrode. In order to ensure that the electrode paste does not have adverse conditions such as soft break, hard break, paste flow, excessive oxidation, U-turn, cracking, etc. during the roasting process, experienced staff are required to carefully operate the submerged arc furnace electrode, add the electrode paste, and lower the electrode. If the operation is improper, it is easy for the electrode paste to segregate in the liquid state formed during the roasting process of 100-500℃. Segregation during the roasting process will cause different densities in different areas of the electrode paste, causing the local electrode barrel to carry too much current, thereby causing the electrode barrel to melt, causing paste flow and soft break of the electrode. On the other hand, if the operation is improperly controlled, it will also cause poor fluidity of the electrode paste, resulting in local voids in the electrode paste during the roasting process, and uneven heating of the electrode barrel, causing the electrode to break. Summary of the invention

[0004] The technical problem to be solved by the present invention is that improper operation is performed when adding electrode paste to the existing ore-fired furnace electrodes, and the electrode paste is easily segregated or cavitated when it forms a liquid during the roasting process, resulting in different electrode paste densities, leading to electrode paste flow and electrode soft fracture.

[0005] In order to solve the above problems, the present invention provides an electrode paste. The raw materials for preparing the electrode paste include, by mass, 71% to 72% of a main material, 26% to 27% of a binder, 0.9% to 3.0% of a nonionic surfactant, and 0.21% to 0.53% of a stabilizer.

[0006] The present invention reduces the surface energy of each component in the liquid formed during the low-temperature roasting process of the electrode paste by adding a nonionic surfactant to the electrode paste, so that the components of the electrode paste are more easily dispersed and flowed, thereby improving its fluidity, facilitating the uniform distribution of the electrode paste during the roasting process, and ensuring the uniformity of the electrode structure. Therefore, it is possible to avoid the problem of voids in the electrode paste due to uneven fluidity during the roasting process, and avoid the problem of uneven density of the electrode paste caused by the voids, and causing the electrode to break due to uneven local heating of the electrode.

[0007] In order to prevent excessive fluidity, the present invention further adds a stabilizer, which can interact with the components in the electrode paste to adjust its fluidity. The electrode paste maintains appropriate fluidity during the calcination process to prevent the electrode paste from segregating due to excessive fluidity. The stabilizer can enhance the overall stability of the electrode paste, making it less likely to undergo structural changes during high-temperature calcination, and ensuring that the electrode paste forms a uniform and dense electrode structure after calcination.

[0008] According to the electrode paste of the present invention, preferably, the main ingredients include, by mass: 100 parts of calcined anthracite, 48 to 56 parts of calcined petroleum coke, and 10 to 14 parts of graphite.

[0009] According to the electrode paste of the present invention, preferably, the binder comprises 25 to 36 parts of tar and 25 to 36 parts of medium-temperature coal tar in parts by mass.

[0010] According to the electrode paste of the present invention, preferably, the nonionic surfactant includes at least one of sorbitan laurate, sorbitan stearate and sorbitan oleate, and preferably, the nonionic surfactant is sorbitan oleate.

[0011] The above nonionic surfactants all have excellent emulsifying, dispersing and wetting properties, and are helpful to improve the dispersibility and fluidity of electrode paste. Among them, sorbitan stearate has a higher melting point, good stability, and is suitable for high temperature environments. Sorbitan oleate has good solubility and better high temperature stability.

[0012] According to the electrode paste of the present invention, preferably, the stabilizer comprises at least one of carboxymethyl cellulose ether, hydroxyethyl cellulose ether and sodium carboxymethyl cellulose.

[0013] The above-mentioned stabilizer has good solubility, thickening and adhesion properties, can increase the viscosity of the electrode paste, help to combine the various components in the electrode paste together, prevent it from falling off or deforming during the roasting process, prevent its excessive fluidity from causing segregation, and help maintain the uniform distribution of the various components in the electrode paste, thereby improving the uniformity and stability of the electrode.

[0014] According to the above-mentioned electrode paste of the present invention, preferably, the raw materials for preparing the electrode paste include, in parts by mass: 100 parts of calcined anthracite, 48 to 56 parts of calcined petroleum coke, 10 to 14 parts of graphite, 25 to 36 parts of tar, 25 to 36 parts of medium-temperature coal tar, 2 to 7 parts of non-ionic surfactant, and 0.5 to 1.2 parts of stabilizer.

[0015] According to the above-mentioned electrode paste of the present invention, preferably, the raw materials for preparing the electrode paste include, by mass: 100 parts of calcined anthracite, 52 parts of calcined petroleum coke, 12 parts of graphite, 30 parts of tar, 30 parts of medium-temperature coal tar, 5 parts of non-ionic surfactant, and 0.8 parts of stabilizer.

[0016] The present invention also provides a method for preparing the electrode paste, comprising:

[0017] Main material mixing: dry-mixing and stirring the crushed main material and stabilizer to obtain a main material mixture;

[0018] Binder mixing: after mixing tar and medium-temperature coal tar, add non-ionic surfactant and continue mixing to obtain a binder mixture;

[0019] Deliquidation and kneading: The main material mixture and the binder mixture are deliquidated and kneaded, and then the electrode paste is obtained after filter pressing and forming.

[0020] The mixing temperature of the dehydration mixing is not higher than 140°C.

[0021] After the main material is crushed, the particle size of the obtained calcined anthracite is ≤15mm, the particle size of the calcined petroleum coke is ≤2mm, and the particle size of the graphite is ≤4mm.

[0022] The beneficial effects of the present invention are:

[0023] The present invention reduces the surface energy of each component in the liquid state formed during the low-temperature calcination of the electrode paste by adding a nonionic surfactant to the electrode paste, so that the components of the electrode paste are more easily dispersed and flowed, thereby improving its fluidity, facilitating the uniform distribution of the electrode paste during the calcination process, and ensuring the uniformity of the electrode structure. Therefore, it is possible to avoid the problem of voids in the electrode paste due to uneven fluidity during the calcination process, and avoid the problem of uneven density of the electrode paste caused by the voids, and causing the electrode to break due to uneven local heating of the electrode.

[0024] In order to prevent excessive fluidity, the present invention further adds a stabilizer, which can interact with the components in the electrode paste to adjust its fluidity. The electrode paste maintains appropriate fluidity during the calcination process to prevent the electrode paste from segregating due to excessive fluidity. The stabilizer can enhance the overall stability of the electrode paste, making it less likely to undergo structural changes during high-temperature calcination, and ensuring that the electrode paste forms a uniform and dense electrode structure after calcination. DETAILED DESCRIPTION

[0025] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0026] The invention provides an electrode paste. The raw materials for preparing the electrode paste include, by weight, 71% to 72% of a main material, 26% to 27% of a binder, 0.9% to 3.0% of a nonionic surfactant, and 0.21% to 0.53% of a stabilizer.

[0027] The main materials include 100 parts by weight of calcined anthracite, 48-56 parts by weight of calcined petroleum coke, and 10-14 parts by weight of graphite. The binder includes 25-36 parts by weight of tar and 25-36 parts by weight of medium-temperature coal tar.

[0028] That is to say, the raw materials for preparing the electrode paste include, by mass, 100 parts of calcined anthracite, 48 to 56 parts of calcined petroleum coke, 10 to 14 parts of graphite, 25 to 36 parts of tar, 25 to 36 parts of medium-temperature coal tar, 2 to 7 parts of non-ionic surfactant, and 0.5 to 1.2 parts of stabilizer. In a preferred embodiment, the raw materials for preparing the electrode paste include, by mass, 100 parts of calcined anthracite, 52 parts of calcined petroleum coke, 12 parts of graphite, 30 parts of tar, 30 parts of medium-temperature coal tar, 5 parts of non-ionic surfactant, and 0.8 parts of stabilizer.

[0029] The optional nonionic surfactant of the present invention includes: at least one of sorbitan laurate, sorbitan stearate, and sorbitan oleate. Preferably, the nonionic surfactant is sorbitan oleate. The factors considered in selecting the nonionic surfactant mainly include its emulsification, dispersion, wetting properties in the electrode paste and its high temperature stability. The above nonionic surfactants all meet the requirements of this application.

[0030] The optional stabilizer of the present invention includes at least one of carboxymethyl cellulose ether, hydroxyethyl cellulose ether and sodium carboxymethyl cellulose. The factors to be considered in selecting the stabilizer mainly include its solubility, thickening, adhesion and high temperature stability in the electrode paste. The above stabilizers all meet the requirements of this application.

[0031] Before preparing the electrode paste, the main material is crushed. After the main material is crushed, the particle size of the calcined anthracite is ≤15mm, the particle size of the calcined petroleum coke is ≤2mm, and the particle size of the graphite is ≤4mm.

[0032] The method for preparing electrode paste of the present invention specifically comprises:

[0033] Main material mixing: dry-mixing and stirring the crushed main material and stabilizer to obtain a main material mixture;

[0034] Binder mixing: after mixing tar and medium-temperature coal tar, add non-ionic surfactant and continue mixing to obtain a binder mixture;

[0035] Deliquidation and kneading: The main material mixture and the binder mixture are deliquidated and kneaded, and then the electrode paste is obtained after filter pressing and forming.

[0036] The mixing temperature of the dehydration mixing is not higher than 140°C.

[0037] The present invention is described below by means of specific examples.

[0038] Embodiment 1:

[0039] Main material mixing: 100 parts of calcined anthracite, 52 parts of calcined petroleum coke and 12 parts of graphite obtained after crushing are poured into a blender and mixed thoroughly, and then 0.8 parts of carboxymethyl cellulose ether is added and mixed thoroughly to obtain a main material mixture.

[0040] Binder mixing: After 30 parts of tar and 30 parts of medium-temperature coal tar are fully mixed in another mixer, 5 parts of sorbitan oleate are added and continued to mix to obtain a binder mixture.

[0041] Deliquidation and kneading: slowly add the main material mixture into the binder mixture, and continue to stir and knead the main material mixture during the process of adding. When the main material mixture is completely added to the binder mixture, heat it to 130°C and continue kneading for 3 hours. Then pour the kneaded material from the kneading pot, roll it in a mold to obtain the electrode paste.

[0042] Example 2 to Example 3: The difference from Example 1 is that the proportions of raw material components are different, see Table 1 for details.

[0043] Comparative Example 1: The difference from Example 1 is that no nonionic surfactant is added, see Table 1 for details.

[0044] Comparative Example 2: The difference from Example 1 is that no stabilizer is added, see Table 1 for details.

[0045] Comparative Example 3: The difference from Example 1 is that no nonionic surfactant and stabilizer are added, see Table 1 for details.

[0046] Table 1 Control table of ingredients in various embodiments and comparative examples

[0047]

[0048] The electrode pastes prepared in the above examples and comparative examples were subjected to performance tests, and the test methods were as follows:

[0049] The determination of compressive strength refers to the "Determination Method of Compressive Strength of Carbon Materials" (GB / T1431-2009);

[0050] The determination of bulk density refers to the "Determination Method of Bulk Density of Carbon Materials" (GB / T24528-2009);

[0051] The determination of resistivity refers to the "Determination Method of Resistivity of Carbon Materials" (GB / T24525-2009);

[0052] The determination of elongation shall refer to the "Test Method for Elongation of Electrode Paste" (YB / T5289-2001);

[0053] The fluidity determination method is as follows: take 200g of raw electrode paste and place it in the electrode paste fluidity measuring instrument, and then place the electrode paste fluidity measuring instrument containing the raw electrode paste in a resistance box at 300±5℃ for 45 minutes, so that the electrode paste melts at high temperature and then flows into the bottom plate of the electrode paste fluidity measuring instrument. The measured fluidity coefficient D is:

[0054] D=φ1 / φ2,

[0055] φ1 is the average diameter of the sample that falls on the bottom plate;

[0056] φ2 is the diameter of the feed opening of the measuring instrument;

[0057] Measure 10 samples continuously, calculate the average value, and record the maximum and minimum values.

[0058] When the flow coefficient of the electrode paste is greater than 2.0, the fluidity of the electrode paste is too large, and particle segregation and stratification are likely to occur. The particles will be squeezed out from the weak points of the electrode tube and easily cause paste flow. When the flow coefficient is less than 1.0, the fluidity of the electrode paste is too low. During use, the paste does not have sufficient fluidity, voids will form, and suspended materials are likely to occur.

[0059] The above performance test results are detailed in Table 2.

[0060] Table 2 Performance test results of electrode paste obtained in various embodiments and comparative examples

[0061]

[0062] It can be seen from Table 2 that the electrode pastes obtained in Examples 1 to 3 are all well prepared, with the average value of the fluidity index being between 1.4 and 1.6, the minimum being 1.39, and the maximum being 1.68, all being between 1 and 2. This indicates that the electrode pastes obtained in Examples 1 to 3 of the present invention have better fluidity during the low-temperature calcination stage, and the probability of electrode paste segregation or local voids is low.

[0063] Comparative Example 1 does not add non-ionic surfactant, resulting in poor fluidity of the electrode paste obtained in Comparative Example 1, with an average value of less than 1, and poor elongation. It can be inferred that during the low-temperature calcination process of the electrode paste obtained in Comparative Example 1, improper operation is prone to cause voids in the electrode paste, resulting in uneven heating of the electrode and causing electrode breakage.

[0064] No stabilizer is added in Comparative Example 2, resulting in the electrode paste obtained in Comparative Example 1 having a relatively high fluidity and a relatively high elongation. It can be inferred that during the low-temperature calcination process, the electrode paste obtained in Comparative Example 1 is prone to electrode paste segregation due to improper operation, which will lead to different densities in different regions of the electrode paste, causing the local electrode barrel to carry too much current, thereby causing the electrode barrel to melt, resulting in paste flow and soft fracture of the electrode.

[0065] Comparative Example 3 does not add non-ionic surfactants and stabilizers. Although the average value of the fluidity index is between 1 and 2, the minimum value is less than 1 and the maximum value is greater than 2, indicating that the electrode paste product obtained in Comparative Example 3 has poor uniformity. During the electrode roasting process, the staff needs to operate with caution, otherwise voids or segregation will occur in the electrode paste.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An electrode paste, characterized in that: The raw materials for preparing the electrode paste include, by weight: 71% to 72% main material, 26% to 27% binder, 0.9% to 3.0% non-ionic surfactant, and 0.21% to 0.53% stabilizer.

2. The electrode paste according to claim 1, characterized in that: The main materials include, by weight: 100 parts of calcined anthracite, 48 to 56 parts of calcined petroleum coke, and 10 to 14 parts of graphite.

3. The electrode paste according to any one of claims 1 or 2, characterized in that: The binder includes 25 to 36 parts of tar and 25 to 36 parts of medium-temperature coal tar in parts by mass.

4. The electrode paste according to claim 3, characterized in that: The nonionic surfactant includes: at least one of sorbitan laurate, sorbitan stearate, and sorbitan oleate. Preferably, the nonionic surfactant is sorbitan oleate.

5. The electrode paste according to any one of claims 1, 3 or 4, characterized in that: The stabilizer comprises at least one of carboxymethyl cellulose ether, hydroxyethyl cellulose ether and sodium carboxymethyl cellulose.

6. The electrode paste according to claim 5, characterized in that: The raw materials for preparing the electrode paste include, by mass, 100 parts of calcined anthracite, 48-56 parts of calcined petroleum coke, 10-14 parts of graphite, 25-36 parts of tar, 25-36 parts of medium-temperature coal tar, 2-7 parts of nonionic surfactant, and 0.5-1.2 parts of stabilizer.

7. The electrode paste according to claim 6, characterized in that: The raw materials for preparing the electrode paste include, by mass, 100 parts of calcined anthracite, 52 parts of calcined petroleum coke, 12 parts of graphite, 30 parts of tar, 30 parts of medium-temperature coal tar, 5 parts of nonionic surfactant, and 0.8 parts of stabilizer.

8. A method for preparing the electrode paste according to claim 1, characterized in that: include: Main material mixing: dry-mixing and stirring the crushed main material and stabilizer to obtain a main material mixture; Binder mixing: after mixing tar and medium-temperature coal tar, add non-ionic surfactant and continue mixing to obtain a binder mixture; Deliquidation and kneading: The main material mixture and the binder mixture are deliquidated and kneaded, and then the electrode paste is obtained after filter pressing and forming.

9. The method according to claim 6, characterized in that The mixing temperature of the dehydration mixing is not higher than 140°C.

10. The electrode paste according to any one of claims 6 or 7, characterized in that: After the main material is crushed, the particle size of the obtained calcined anthracite is ≤15mm, the particle size of the calcined petroleum coke is ≤2mm, and the particle size of the graphite is ≤4mm.

Citation Information

Cited By

  • Preparation method of modified coal pitch and preparation method of carbon material

    CN121379188A